Kajian Peran Kepolisian dalam Melindungi Anak Korban Perundungan melalui Implementasi Mediasi Restorative Justice di Gorontalo - Laita, Rivan Hasan; Abdussamad, Zamroni; Mantali, Avelia Rahmah Y. (CV. Era Digital Nusantara, 2025)
The increase in bullying cases among children, particularly in the Gorontalo region, has raised serious concerns regarding legal protection and the psychological impact experienced by victims. This study aims to analyze the effectiveness of the law in providing protection for children as victims of bullying from a victimology perspective, as well as to assess the implementation of mediation or restorative justice systems applied by law enforcement officials. The method used is empirical legal research with a qualitative approach, involving observation, interviews with police officers, victims, perpetrators, and documentation studies at the Gorontalo Police Headquarters and the Women's Empowerment and Child Protection Agency. The findings of the study indicate that the role of the police in child protection has been carried out through preventive and repressive measures, but there are still obstacles in coordination between institutions and low public awareness. The mediation system or restorative justice is considered to offer a more humane alternative resolution, but its effectiveness heavily depends on the understanding and readiness of all parties involved. The implications of this study emphasize the need for strengthened education, improved capacity of law enforcement officials, and cross-sectoral collaboration to create an adaptive and responsive legal protection system for child bullying victims in Indonesia, particularly in Gorontalo.